Learning Disabilities in Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1991)
Neurophysiological mechanisms by which epilepsy may interfere with learning ability are reviewed from the Department of Clinical Neurophysiology, Mauds ley Hospital, and Department of Psychology, Middlesex Hospital, London, England.